Continuous Ambulatory Peritoneal Dialysis Cost-Effectiveness in National Health Insurance Era of Indonesia - Tjahjodjati, Tjahjodjati; Kuddah, Yasser; Wijayanti, Zola (Majalah Kedokteran Bandung, 2023)
Essential treatments for patients with end-stage renal disease include Renal Replacement Therapy (RRT) consisting of hemodialysis, peritoneal dialysis, and kidney transplantation. In 2014, dialysis coverage in Indonesia was more than 1.5 trillion, making it the second highest expense in the National Health Insurance (BPJS) expenses. This study compared the cost-effectiveness between Continuous Ambulatory Peritoneal Dialysis (CAPD) and Hemodialysis (HD) in  patients treated in Dr. Hasan Sadikin General Hospital. Data were collected from the Urology Department from 2014 to 2017. This was a retrospective observational study on 3 groups of patients: patients with effective CAPD each year as the first group; patients who had experienced repair of CAPD and continued to use it as the second group; and patients who discontinued CAPD due to complications and returned to hemodialysis as the third group. Each group expense was calculated with standard cost insurance for one year in  the hospital. The expense was then be compared to the expense of hemodialysis for one year. A total of 89 patients in the CAPD program from 2014–2017 were treated at the department. When compared to HD, the first, second, and third group of CAPD patients experienced a cost reduction of IDR 23.227.857/person, IDR 18.127.857/person, and IDR 1.661.972.000, respectively. Total savings from the CAPD program in the hospital was IDR 1.661.972.000 from 2014. It is then concluded that CAPD could reduce the burden of government insurance in a cost-effective manner and is considered a treatment of choice in the National Health Insurance Era.